Wide-temperature-range lithium / carbon fluoride battery, positive electrode material and electrolyte

The treatment of fluorinated carbon positive electrode materials and optimized electrolyte composition through plasma chemical vapor deposition technology solves the problem of poor performance of lithium/fluorinated carbon batteries at extreme temperatures, and achieves battery performance with high energy density and power density in a wide temperature range, which promotes its application in the special defense and military field.

CN119601697AActive Publication Date: 2025-03-11NANKAI UNIV
View PDF 22 Cites 0 Cited by

Patent Information

Application Number
CN202411398561.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-11
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Lithium/carbon fluoride cells exhibit low energy density and power density at extreme temperatures, and have problems with electrode/electrolyte interface instability and electrolyte volatility at high temperatures, limiting their application in wide temperature environments.

Method used

Plasma chemical vapor deposition technology is used to treat fluorinated carbon positive electrode materials, and thin layer materials with surface covered with nanocarbon dots and mesoporous richness are prepared, and electrolyte composed of lithium tetrafluoroborate, methyl acetate and dimethyl sulfite are combined to optimize the composition and structure of fluorinated carbon positive electrode materials and electrolyte to improve the performance of the battery in a wide temperature range.

Benefits of technology

It has achieved that lithium/fluorinated carbon batteries have high energy density and power density in a wide temperature range of -100~100℃, and achieved high energy density at extremely low temperatures of -50℃ and -70℃, which has enhanced the application potential of batteries in the special national defense and military field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601697A_ABST
    Figure CN119601697A_ABST
Patent Text Reader

Abstract

The invention discloses a wide-temperature-range lithium / carbon fluoride battery, a positive electrode material and an electrolyte. The battery comprises a positive electrode, a negative electrode, a diaphragm and an electrolyte, the positive electrode comprises a carbon fluoride positive electrode material, and a preparation method of the carbon fluoride positive electrode material comprises the following steps: placing carbon fluoride in a plasma chemical vapor deposition furnace, keeping vacuum, introducing a carbon source gas into the plasma chemical vapor deposition furnace, controlling the radio frequency power to be 100-200W, controlling the heat treatment temperature to be 550-600 DEG C, and maintaining the heat treatment temperature to be 550-600 DEG C; the electrolyte is prepared from lithium tetrafluoroborate, methyl acetate and dimethyl sulfite, the volume ratio of the methyl acetate to the dimethyl sulfite is 1: 1, and the concentration of the lithium tetrafluoroborate is 1 mol / L. The invention further discloses a preparation method of the carbon fluoride cathode material. The battery disclosed by the invention can stably work in a range of-100 DEG C to 100 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of primary batteries, and in particular relates to a wide-temperature range lithium / carbon fluoride battery, a positive electrode material and an electrolyte. Background Art

[0002] Lithium / carbon fluoride (Li / CF x ) Primary batteries are favored by researchers among many primary batteries due to their high theoretical energy density (2100Wh / kg, x=1), stable working voltage, long storage life, wide stable use range, good safety and other advantages. They are widely used in special national defense and military fields such as military equipment (single-soldier combat systems, electronic test equipment, missile ignition systems, submarines, etc.), deep sea / deep space exploration, polar exploration, and long space exploration. However, these fields have strict requirements on the performance of power systems at extreme temperatures (such as Mars exploration (~-100℃), oil exploration (~100℃)), so the development of lithium / carbon fluoride batteries for use at extreme temperatures has scientific and practical significance.

[0003] Lithium / carbon fluoride batteries undergo the following discharge process: Li + Transport in the electrolyte bulk; Li + Desolvation at the electrode / electrolyte interface; Li + Conducting in the positive electrode solid electrolyte layer (CEI); Li + In CF x Interlayer diffusion; CF bond breaking. At low temperatures, the electrolyte ion conductivity decreases, the viscosity increases, and even freezes, causing Li + Liquid phase transport is limited; unstable CEI is generated at the carbon fluoride cathode / electrolyte interface, resulting in Li + The difficulty of desolvation limits the ion interface conduction; the inherent insulation of carbon fluoride cathode materials leads to their low ion / electronic conductivity, which limits the Li + Solid phase diffusion, these factors synergistically induce the lithium fluoride produced by discharge to accumulate on the surface and edge of the carbon fluoride positive electrode material, blocking the ion transmission channel, resulting in low energy density and power density of lithium / carbon fluoride batteries. At high temperatures, due to the lack of a stable electrode / electrolyte interface, the solvent is easy to decompose and produce serious side reactions, and the solvent is easy to volatilize and consume the electrolyte, causing battery failure. These factors seriously restrict the use of lithium / carbon fluoride batteries in a wide temperature range environment.

[0004] Based on the above analysis, carbon fluoride positive electrode materials and electrolytes are equally important to the electrochemical performance of batteries at extreme temperatures. Therefore, how to develop a carbon fluoride positive electrode material and electrolyte that can simultaneously take into account the high and low temperature performance of lithium / carbon fluoride batteries is of great significance to promoting the application of lithium / carbon fluoride batteries in special national defense and military fields. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a wide temperature range lithium / carbon fluoride battery, anode material and electrolyte, which have high energy density and power density in a wide temperature range (-100 to 100°C). At the same time, the assembled Ah-level soft-pack battery can achieve a high energy density of 470Wh / kg and 333Wh / kg (based on the overall mass of the battery) at extremely low temperatures of -50°C and -70°C.

[0006] The technical solution of the present invention to solve the technical problem is:

[0007] A first aspect of the present invention provides a wide temperature range lithium / carbon fluoride battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte.

[0008] The positive electrode comprises a fluorinated carbon positive electrode material, and the preparation method of the fluorinated carbon positive electrode material is:

[0009] The carbon fluoride is placed in a plasma chemical vapor deposition furnace, and the plasma chemical vapor deposition furnace is kept in vacuum by a vacuum pump; acetylene or methane is introduced into the plasma chemical vapor deposition furnace, and the radio frequency power is controlled to be 100-200W, the heat treatment temperature is 550-600°C, and the heat treatment time is 10-20min to obtain a carbon fluoride positive electrode material, wherein the carbon fluoride positive electrode material is a thin layer material with nano-carbon dots and rich mesopores on the surface, wherein the carbon fluoride thin layer material has a length and width of 5-50μm and a thickness of 0.2-20μm, the diameter of the nano-carbon dots on the surface of the thin layer is 5-20nm, and the diameter of the mesopores is 2-50nm.

[0010] The electrolyte consists of lithium tetrafluoroborate, methyl acetate and dimethyl sulfite, the volume ratio of methyl acetate to dimethyl sulfite is 1:1, and the concentration of lithium tetrafluoroborate is 1 mol / L.

[0011] Furthermore, the positive electrode is prepared by dispersing a carbon fluoride positive electrode material, conductive carbon black and a binder PVDF in a mass ratio of 8 to 9: 0.5 to 1: 0.5 to 1 (preferably 8: 1: 1; for Ah-class soft-pack batteries, the ratio is 9: 0.5: 0.5) in N-methylpyrrolidone, fully mixing the mixture, coating the mixture on a carbon-coated aluminum foil and drying the mixture.

[0012] Furthermore, the negative electrode is a lithium sheet or a lithium belt with a thickness of 50 to 500 μm.

[0013] Furthermore, the separator is a PE separator (thickness 25 μm).

[0014] The second aspect of the present invention is to provide a positive electrode material for a wide temperature range lithium / carbon fluoride battery, wherein the carbon fluoride positive electrode material is a thin layer material with a surface covered with nanocarbon dots and rich in mesopores, wherein the carbon fluoride thin layer material has a length and width of 5 to 50 μm, a thickness of 0.2 to 20 μm, a diameter of nanocarbon dots on the surface of the thin layer of 5 to 20 nm, and a mesopore diameter of 2 to 50 nm. The preparation method is: placing carbon fluoride in a plasma chemical vapor deposition furnace, and adjusting the commercial carbon fluoride positive electrode material to be 10 to 50 cm away from the plasma radio frequency coil. The plasma chemical vapor deposition furnace is kept vacuum by a vacuum pump; the carbon source atmosphere is introduced into the plasma chemical vapor deposition furnace, the radio frequency power is controlled to be 50 to 200 W, the heat treatment temperature is 300 to 600 ° C, and the heat treatment time is 5 to 30 min to obtain a carbon fluoride positive electrode material.

[0015] The carbon fluoride material in the present invention has a large specific surface area, rich thin layers and pore structures, which are conducive to the full infiltration of the electrolyte and promote the rapid conduction of lithium ions; at the same time, the carbon fluoride surface contains a large number of nano-carbon dots, which improves the electronic conductivity of the material itself, reduces the polarization during the discharge process, and greatly improves the utilization rate of the carbon fluoride material at high rates and low temperatures.

[0016] Furthermore, the carbon source atmosphere is acetylene or methane.

[0017] Further, the RF power is 100-200W, the heat treatment temperature is 550-600°C, and the heat treatment time is 10-20min. Preferably, the RF power is 150W, the heat treatment temperature is 580°C, and the heat treatment time is 15min.

[0018] The present invention uses plasma chemical vapor deposition technology to process commercial fluorinated carbon materials, and has the following outstanding technical effects: (1) By controlling the plasma radio frequency power, radio frequency treatment time and heating time, a fluorinated carbon material with uniform pore distribution, thinner layers and larger specific surface area can be obtained; (2) By controlling different carrier gas components and gas flow rates, the size and number of carbon nanodots on the surface of the fluorinated carbon can be effectively controlled. (3) The method is simple and easy to operate, and is convenient for large-scale application. The fluorinated carbon material with a large specific surface area, rich pore size and a large number of carbon nanodots has high ionic / electronic conductivity, effectively reduces polarization, and improves the rate performance and low-temperature performance of the fluorinated carbon material.

[0019] The third aspect of the present invention provides a wide temperature range lithium / carbon fluoride battery electrolyte, which is composed of lithium tetrafluoroborate, a carboxylate solvent and a sulfite solvent. The carboxylate solvent is methyl formate, methyl acetate, ethyl acetate, methyl propionate, and ethyl propionate; the sulfite solvent is dimethyl sulfite or diethyl sulfite.

[0020] Furthermore, the concentration of lithium tetrafluoroborate is 0.5-4 mol / L; the volume ratio of the carboxylic acid lipid solvent to the sulfite solvent is 1-0:0-1.

[0021] Preferably, the concentration of lithium tetrafluoroborate is 1 mol / L, the carboxylate solvent is methyl acetate, the sulfite solvent is dimethyl sulfite, and the volume ratio of methyl acetate to dimethyl sulfite is 1:1.

[0022] Preferably, the electrolyte is prepared by uniformly mixing a carboxylic acid ester solvent and a sulfite solvent to form a co-solvent; and then adding lithium tetrafluoroborate and dissolving the lithium tetrafluoroborate to obtain the electrolyte.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention compares the treatment of carbon fluoride by plasma chemical vapor deposition under different atmosphere conditions, and finds that the surface of the carbon fluoride material treated with inert gas contains a large number of pores, and the specific surface area increases; the pore size / specific surface area of ​​the carbon fluoride material treated with carbon source atmosphere is further enlarged, and a large number of carbon nanodots grow on the surface of the material, which significantly improves the electronic / ionic conductivity of the carbon fluoride material and promotes the Li + Diffusion within the fluorinated carbon.

[0025] (2) Based on the viscosity effect and dielectric effect, the present invention screened carboxylic acid ester solvents with low viscosity and sulfite solvents with high dielectric constant as wide temperature range electrolytes. Carboxylic acid ester solvents have low viscosity and low freezing point, which can promote ion diffusion of electrolytes at low temperatures. Sulfite solvents have high dielectric constants and wide liquid ranges, which can prevent salt precipitation at low temperatures and electrolyte volatilization at high temperatures; sulfite solvents with high adsorption energy and high HOMO energy levels can be adsorbed on the surface of the fluorinated carbon positive electrode, inducing decomposition at high potential to produce a solid electrolyte layer rich in organic sulfur components, accelerating Li + During the discharge process, the solid electrolyte layer evolves into inorganic lithium sulfide / lithium fluoride-rich components, further accelerating the Li + Rapid conduction in the interface layer improves the kinetic performance of lithium / carbon fluoride batteries at low temperatures and improves their stability at high temperatures; at the same time, sulfite solvents with low LUMO energy levels can relay the reaction at the low potential of carbon fluoride at the end of discharge, further oxidatively decompose to provide capacity, and improve the overall energy density of the battery.

[0026] (3) Based on the carbon fluoride cathode material and electrolyte described in the present invention, the lithium / carbon fluoride full battery composed of a matching metal lithium anode has a high energy density and power density in a wide temperature range (-100 to 100°C). The Ah-level soft-pack battery assembled at the same time can achieve a high energy density of 470Wh / kg and 333Wh / kg (based on the overall mass of the battery) at extremely low temperatures of -50°C and -70°C, which is of great significance to promoting the application of lithium / carbon fluoride batteries in special defense and military fields.

[0027] (4) The fluorinated carbon cathode material provided by the present invention has a relatively mature preparation method and process, and can be mass-produced. The electrolyte component provided by the present invention has the advantages of low cost, easy preparation, safety and no pollution, and can be applied on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a transmission electron micrograph of the commercial untreated carbon fluoride material of Comparative Example 1;

[0029] Figure 2 This is a transmission electron microscope image of the carbon fluoride positive electrode material prepared in Comparative Example 2;

[0030] Figure 3 This is a transmission electron microscope image of the carbon fluoride positive electrode material prepared in Comparative Example 3;

[0031] Figure 4 This is a transmission electron microscope image of the carbon fluoride positive electrode material prepared in Example 1;

[0032] Figure 5 XRD comparison diagram of carbon fluoride positive electrode materials prepared in Example 1 and Comparative Examples 1-3;

[0033] Figure 6 BET comparison diagram of carbon fluoride positive electrode materials prepared in Example 1 and Comparative Examples 1-3;

[0034] Figure 7 This is a comparison chart of infrared spectra of carbon fluoride positive electrode materials prepared in Example 1 and Comparative Examples 1-3;

[0035] Figure 8 A comparison chart of the contents of semi-ionic CF bonds in XPS characterization of fluorinated carbon positive electrode materials prepared in Example 1 and Comparative Examples 1-3;

[0036] Fig. 9 The discharge curves of the batteries of Example 2 and Comparative Examples 4-6 at 0.1 A / g;

[0037] Fig.10 The discharge curves of the batteries of Example 2 and Comparative Examples 4-6 at 5 A / g;

[0038] Fig.11It is the XRD comparison diagram of Example 3 and Comparative Examples 7-9 and Comparative Example 1;

[0039] Fig.12 The discharge curves of the batteries of Example 4 and Comparative Examples 10-11 at 1C rate;

[0040] Fig.13 The discharge curves of the batteries of Example 5 and Comparative Examples 12-13 at a rate of 0.1C are shown;

[0041] Fig.14 It is a comparison diagram of differential scanning calorimetry analysis of Example 6 and Comparative Examples 14-17;

[0042] Fig.15 It is a comparison diagram of ionic conductivity of Example 6 and Comparative Examples 14-17 at different temperatures;

[0043] Fig.16 This is a comparison chart of the viscosities of Example 6 and Comparative Examples 14-17 at different temperatures;

[0044] Fig.17 is a discharge curve diagram of the battery of Example 7 at -100-100°C;

[0045] Fig.18 is a discharge curve diagram of the battery of Example 7 at 25° C. and different current densities;

[0046] Fig.19 The discharge curves of the battery of Example 7 at -30°C and different current densities;

[0047] Fig. 20 The discharge curves of the battery of Example 7 at -50°C and different current densities;

[0048] Fig.21 The discharge curves of the battery of Example 7 at -70°C and different current densities;

[0049] Fig. 22 The discharge curves of the battery of Example 7 at -86°C and different current densities;

[0050] Fig.23 is a discharge curve diagram of the battery of Example 8 at -50°C and -70°C;

[0051] Fig.24 This is a comparison chart of the contents of CF bonds, SF bonds and LiF in the XPS characterization of the electrode surface of Example 9;

[0052] Fig.25 This is a comparison chart of the contents of Li2S and ROSOLi in the XPS characterization of the pole piece surface of Example 9;

[0053] Fig.26 It is a comparison diagram of charge transfer impedance of Example 10 and Comparative Example 18 at -20°C to 25°C;

[0054] Fig. 27 A comparison diagram of lithium ion desolvation energy barriers of Example 10 and Comparative Example 18;

[0055] Fig.28 A comparison diagram of the energy barriers of lithium ions crossing CEI in Example 11 and Comparative Example 19;

[0056] Fig.29 1 is a comparison diagram of the lithium ion desolvation energy barriers of Example 11 and Comparative Example 19. DETAILED DESCRIPTION

[0057] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0058] By comparing the morphology and structure of the carbon fluoride materials in Example 1 and Comparative Examples 1 to 3, the optimal atmosphere for treating carbon fluoride by plasma chemical vapor deposition was confirmed.

[0059] Example 1

[0060] The carbon fluoride cathode material is obtained by plasma chemical vapor deposition, specifically:

[0061] (1) Placing a commercial carbon fluoride cathode material in a plasma chemical vapor deposition furnace; adjusting the commercial carbon fluoride cathode material to be 50 cm away from the plasma radio frequency coil.

[0062] (2) The plasma chemical vapor deposition furnace is kept in vacuum by a vacuum pump.

[0063] (3) introducing acetylene into the plasma chemical vapor deposition furnace that has been evacuated in step (2).

[0064] (4) On the basis of step (3), the radio frequency switch and the heating switch of the plasma chemical vapor deposition furnace are turned on, and the heat treatment time is controlled to obtain the carbon fluoride positive electrode material; the radio frequency power is 150 W, the heat treatment temperature is 580° C., and the heat treatment time is 15 min.

[0065] Comparative Example 1

[0066] Commercial untreated fluorinated carbon material.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that step (3) of Example 1 is omitted.

[0069] Comparative Example 3

[0070] The difference from Example 1 is that the acetylene in step (3) is replaced by argon.

[0071] By performing transmission electron microscopy tests on Example 1 and Comparative Examples 1 to 3 ( Figures 1 to 4 )、X-ray diffraction analysis( Figure 5 )、BET test( Figure 6 )、Infrared spectroscopy analysis( Figure 7 ) and X-ray photoelectron spectroscopy (XPS) ( Figure 8 ), the morphology and structure of carbon fluoride treated in different atmospheres were characterized.

[0072] Depend on Figure 1 It can be seen that the untreated fluorinated carbon has a smooth surface.

[0073] Depend on Figure 2 It can be seen that when heat treatment is performed without passing gas, a large number of wrinkles are generated on the surface of the fluorinated carbon.

[0074] Depend on Figure 3 It can be seen that under the condition of the presence of an inert atmosphere (argon), the surface of the treated carbon fluoride is uneven and has a similar pore structure.

[0075] Depend on Figure 4 It can be seen that in the presence of a carbon source atmosphere (acetylene), a rich pore structure is generated on the surface of the treated fluorinated carbon, and a large number of carbon nanodots grow at the edges.

[0076] Depend on Figure 5 It can be seen that the fluorinated carbon materials obtained by plasma chemical vapor deposition technology under different atmospheres are similar to the commercial fluorinated carbon structures and have not undergone significant changes.

[0077] Depend on Figure 6 It can be seen that the fluorinated carbon materials obtained by plasma chemical vapor deposition technology under different atmospheres have large specific surface areas and pore sizes, among which the effect after treatment with carbon source atmosphere (acetylene) is the best.

[0078] Depend on Figure 7 and Figure 8 It can be seen that the CF bond properties of the fluorinated carbon material obtained by plasma chemical vapor deposition technology under different atmospheres change significantly, the semi-ionic bonds increase, and the conductivity is enhanced. Among them, the effect after treatment with carbon source atmosphere (acetylene) is the best.

[0079] Comparative Example 4 uses untreated commercial carbon fluoride material as the positive electrode active material, and matches the electrolyte, negative electrode and separator to form a lithium / carbon fluoride battery. Example 2 and Comparative Examples 5-6 use the carbon fluoride material obtained by plasma chemical vapor deposition technology under different atmospheres as the positive electrode active material, and matches the electrolyte, negative electrode and separator to form a lithium / carbon fluoride battery.

[0080] Example 2

[0081] The fluorinated carbon material obtained in Example 1 was used as the positive electrode active material.

[0082] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained in Example 1 were mixed uniformly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; the positive electrode slurry was then evenly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0083] Negative electrode: lithium sheet with a diameter of 14 mm and a thickness of 500 μm.

[0084] Diaphragm: PE diaphragm, SK innovation Co. Ltd.

[0085] The electrolyte is composed of lithium hexafluorophosphate, ethylene carbonate and diethyl carbonate; the concentration of lithium hexafluorophosphate is 1 mol / L, and the volume ratio of ethylene carbonate and diethyl carbonate is 1:1. The specific configuration method is: firstly, ethylene carbonate and diethyl carbonate solvents are uniformly mixed to form a co-solvent; then lithium hexafluorophosphate is added and dissolved to obtain the electrolyte.

[0086] Battery assembly: Assemble button cells in the order of negative electrode shell - spring - gasket - negative electrode - electrolyte - diaphragm - electrolyte - positive electrode - positive electrode shell. The battery specification is 2032.

[0087] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0088] Comparative Example 4

[0089] The untreated commercial carbon fluoride material of Comparative Example 1 was used as the positive electrode active material.

[0090] Positive electrode: The untreated commercial fluorinated carbon material, conductive carbon black (Super P) and PVDF of Comparative Example 1 were mixed uniformly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; the positive electrode slurry was then evenly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0091] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0092] Battery assembly: Same as Example 2.

[0093] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0094] Comparative Example 5

[0095] The fluorinated carbon material obtained in Comparative Example 2 was used as the positive electrode active material.

[0096] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained in Comparative Example 2 were mixed uniformly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; the positive electrode slurry was then uniformly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0097] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0098] Battery assembly: Same as Example 2.

[0099] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0100] Comparative Example 6

[0101] The carbon fluoride material obtained in Comparative Example 3 was used as the positive electrode active material.

[0102] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained in Comparative Example 3 were mixed uniformly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; the positive electrode slurry was then uniformly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0103] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0104] Battery assembly: Same as Example 2.

[0105] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0106] Depend on Figures 9-10 It can be seen that the fluorinated carbon material obtained by using Example 1 has the best electrochemical performance. Table 1 is a comparison of the voltage and discharge specific capacity of Example 2 and Comparative Examples 4 to 6 at different rates.

[0107] Table 1

[0108]

[0109] As can be seen from Table 1, Example 2 has the best electrochemical performance at both low and high rates. This is because the fluorinated carbon corresponding to Example 1 has a large pore size / specific surface area, and a large number of carbon nanodots grow on the surface of the material, which significantly improves the electronic / ionic conductivity of the fluorinated carbon material, resulting in improved battery performance.

[0110] Example 3 and Comparative Examples 7 to 9 are fluorinated carbon materials obtained by plasma chemical vapor deposition technology at different temperatures, and the optimal processing temperature is determined by characterizing their structures and electrochemical properties.

[0111] Example 3

[0112] The fluorinated carbon material is obtained by plasma chemical vapor deposition, specifically:

[0113] (1) Placing a commercial carbon fluoride cathode material in a plasma chemical vapor deposition furnace; adjusting the commercial carbon fluoride cathode material to be 40 cm away from the plasma radio frequency coil.

[0114] (2) The plasma chemical vapor deposition furnace is kept in vacuum by a vacuum pump.

[0115] (3) introducing acetylene into the plasma chemical vapor deposition furnace that has been evacuated in step (2).

[0116] (4) On the basis of step (3), the radio frequency switch and the heating switch of the plasma chemical vapor deposition furnace are turned on, and the heat treatment time is controlled to obtain a fluorinated carbon positive electrode material; preferably, the radio frequency power is 150 W, the heat treatment temperature is 580° C., and the heat treatment time is 15 min.

[0117] Comparative Example 7

[0118] The difference from Example 3 is that the heat treatment temperature in step (4) is 500°C.

[0119] Comparative Example 8

[0120] The difference from Example 3 is that the heat treatment temperature in step (4) is 550°C.

[0121] Comparative Example 9

[0122] The difference from Example 3 is that the heat treatment temperature in step (4) is 600°C.

[0123] By performing X-ray diffraction analysis on Example 3 and Comparative Examples 7 to 9 ( Fig.11 ), it was found that when the heat treatment temperature reached 600°C, the basic structure of carbon fluoride changed. Therefore, the preferred temperature range is: 300-580°C. The carbon fluoride materials obtained in Example 3 and Comparative Examples 7-8 were further used as positive electrodes, matched with negative electrodes, separators and electrolytes to assemble lithium / carbon fluoride batteries (see Example 4, Comparative Examples 10-11), and the optimal heat treatment temperature was confirmed by electrochemical performance.

[0124] Example 4

[0125] The fluorinated carbon material obtained in Example 3 was used as the positive electrode active material.

[0126] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained in Example 3 were mixed uniformly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; then the positive electrode slurry was evenly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into a positive electrode with a diameter of 10 mm.

[0127] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0128] Battery assembly: Same as Example 2.

[0129] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0130] Comparative Example 10

[0131] The fluorinated carbon material obtained in Comparative Example 7 was used as the positive electrode active material.

[0132] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained in Comparative Example 7 were mixed uniformly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; the positive electrode slurry was then uniformly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0133] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0134] Battery assembly: Same as Example 2.

[0135] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0136] Comparative Example 11

[0137] The fluorinated carbon material obtained in Comparative Example 8 was used as the positive electrode active material.

[0138] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained in Comparative Example 8 were mixed uniformly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; the positive electrode slurry was then uniformly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0139] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0140] Battery assembly: Same as Example 2.

[0141] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0142] Depend on Fig.12 It can be seen that the fluorinated carbon material obtained by using Example 3 has the best electrochemical performance. It is confirmed that when the heat treatment temperature is 580°C, the fluorinated carbon material obtained by using the plasma chemical vapor deposition technology is the best.

[0143] In Example 5 and Comparative Examples 12 to 13, the carbon fluoride materials obtained by plasma chemical vapor deposition for different times under an acetylene carbon source atmosphere at a heat treatment temperature of 580°C are used as positive electrodes, and electrolytes, negative electrodes and separators are matched to form lithium / carbon fluoride batteries, and the optimal heat treatment time is confirmed by electrochemical performance.

[0144] Example 5

[0145] The fluorinated carbon material is obtained by plasma chemical vapor deposition, specifically:

[0146] (1) Placing a commercial carbon fluoride cathode material in a plasma chemical vapor deposition furnace; adjusting the commercial carbon fluoride cathode material to be 30 cm away from the plasma radio frequency coil.

[0147] (2) The plasma chemical vapor deposition furnace is kept in vacuum by a vacuum pump.

[0148] (3) introducing acetylene into the plasma chemical vapor deposition furnace that has been evacuated in step (2).

[0149] (4) On the basis of step (3), the radio frequency switch and the heating switch of the plasma chemical vapor deposition furnace are turned on, and the heat treatment time is controlled to obtain the carbon fluoride positive electrode material; the radio frequency power is 150 W, the heat treatment temperature is 580° C., and the heat treatment time is 15 min.

[0150] The fluorinated carbon material treated in the above manner is used as a positive electrode active material.

[0151] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained after the above treatment were mixed evenly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; then the positive electrode slurry was evenly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0152] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0153] Battery assembly: Same as Example 2.

[0154] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0155] Comparative Example 12

[0156] The difference from Example 5 is that the heat treatment time in step (4) is 10 minutes.

[0157] The fluorinated carbon material treated in the above manner is used as a positive electrode active material.

[0158] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained after the above treatment were mixed evenly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; then the positive electrode slurry was evenly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0159] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0160] Battery assembly: Same as Example 2.

[0161] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0162] Comparative Example 13

[0163] The difference from Example 5 is that the heat treatment time in step (4) is 25 minutes.

[0164] The fluorinated carbon material treated in the above manner is used as a positive electrode active material.

[0165] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained after the above treatment were mixed evenly in a mass ratio of 8:1:1, dispersed in N-methylpyrrolidone, and fully stirred for 8 hours to obtain a positive electrode slurry; then the positive electrode slurry was evenly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into positive electrodes with a diameter of 10 mm.

[0166] The negative electrode, separator and electrolyte are the same as those in Example 2.

[0167] Battery assembly: Same as Example 2.

[0168] After the assembled battery was left to rest for 10 hours, a discharge test was performed at room temperature with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0169] Depend on Fig.13 It can be seen that Example 5 has relatively high specific capacity and voltage, so the fluorinated carbon material obtained by Example 5 has the best performance. It is confirmed that when the heat treatment temperature is 580° C., the optimal time for treating fluorinated carbon using plasma chemical vapor deposition technology is 15 minutes.

[0170] The optimal electrolyte composition ratio was screened out by comparing the freezing points of Example 6 and Comparative Examples 14 to 17, as well as the ionic conductivity and viscosity at different temperatures.

[0171] Example 6

[0172] The electrolyte consists of lithium tetrafluoroborate, methyl acetate and dimethyl sulfite; the concentration of lithium tetrafluoroborate is 1 mol / L; and the volume ratio of methyl acetate to dimethyl sulfite is 1:1.

[0173] The specific configuration method is: first, methyl acetate and dimethyl sulfite are uniformly mixed in a volume ratio of 1:1 to form a co-solvent; then, lithium tetrafluoroborate is added, and after dissolution, a uniform electrolyte having a lithium tetrafluoroborate concentration of 1 mol / L is obtained.

[0174] Comparative Example 14

[0175] The electrolyte consists of lithium tetrafluoroborate and methyl acetate; the concentration of lithium tetrafluoroborate is 1 mol / L;

[0176] The specific configuration method is: dissolving lithium tetrafluoroborate in methyl acetate to obtain a uniform electrolyte with a lithium tetrafluoroborate concentration of 1 mol / L.

[0177] Comparative Example 15

[0178] The electrolyte consists of lithium tetrafluoroborate, methyl acetate and dimethyl sulfite; the concentration of lithium tetrafluoroborate is 1 mol / L; and the volume ratio of methyl acetate to dimethyl sulfite is 7:3.

[0179] Comparative Example 16

[0180] The electrolyte consists of lithium tetrafluoroborate, methyl acetate and dimethyl sulfite; the concentration of lithium tetrafluoroborate is 1 mol / L; and the volume ratio of methyl acetate to dimethyl sulfite is 3:7.

[0181] Comparative Example 17

[0182] The electrolyte consists of lithium tetrafluoroborate and dimethyl sulfite; the concentration of lithium tetrafluoroborate is 1 mol / L;

[0183] The specific configuration method is: dissolving lithium tetrafluoroborate in dimethyl sulfite to obtain a uniform electrolyte with a lithium tetrafluoroborate concentration of 1 mol / L.

[0184] By performing differential scanning calorimetry analysis ( Fig.14 )、AC impedance analysis( Fig.15 ) and viscosity test ( Fig.16 ), the freezing point of electrolytes with different compositions and their ionic conductivity and viscosity at different temperatures are characterized.

[0185] Depend on Fig.14 It can be seen that when the volume ratio of methyl acetate to dimethyl sulfite is 0-7:3-10, the freezing point of the electrolyte is less than -100°C. Figures 15-16 When the volume ratio of methyl acetate to dimethyl sulfite is 1:1 (Example 6), it exhibits the best ionic conductivity in the range of -80 to 30°C and the lowest viscosity in the range of -40 to 30°C, and is the electrolyte with the best comprehensive performance.

[0186] The positive electrode in Example 5 was matched with the electrolyte, negative electrode and separator of Example 6 to assemble a lithium / carbon fluoride battery, and its electrochemical performance in a wide temperature range was tested.

[0187] Example 7

[0188] Positive electrode: The same as the positive electrode in Example 5.

[0189] Electrolyte: The electrolyte of Example 6 was used.

[0190] The negative electrode and separator are the same as those in Example 2.

[0191] Battery assembly: Same as Example 2.

[0192] After the assembled battery has been allowed to stand for 10 hours, it is tested over a wide temperature range of -100 to 100°C, with the battery discharged at a constant current density of 5mA / g or 10mA / g for 2 hours or 4 hours. For a wide temperature range test of 25 to -86°C, the discharge test is carried out with a cutoff voltage of 1.5V, and the discharge specific capacity of the battery is calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0193] Depend on Fig.17 It can be seen that the positive electrode of Example 5 and the electrolyte of Example 6 can work stably in a wide temperature range of -100 to 100°C. Figures 18 to 22 It can be seen that the positive electrode of Example 5 matched with the electrolyte of Example 6 has high discharge specific capacity and rate performance in the temperature range of -86 to 25°C. And at a small current density, it shows a discharge specific capacity exceeding the theoretical capacity, that is, a slope platform appears after the carbon fluoride discharge platform, corresponding to the decomposition of dimethyl sulfite, indicating that the electrolyte has a capacity contribution effect, and can relay the reaction after the carbon fluoride completes the discharge, further improving the battery energy density. Table 2 shows the discharge performance of the battery of Example 7 at different temperatures.

[0194] Table 2

[0195]

[0196]

[0197] It can be seen from Table 2 that Example 7 has excellent energy density and power density in the temperature range of -86 to 25°C. Specifically, at 25°C, the battery can operate at a high current density of 50A / g, and achieve an energy density of 1099Wh / kg and a power density of 86kW / kg (based on the mass of active materials); at -30°C, the battery can operate at a high current density of 5A / g, and achieve an energy density of 976Wh / kg and a power density of 9220W / kg (based on the mass of active materials); at -50°C, the battery can operate at a high current density of 2A / g, and achieve an energy density of 765Wh / kg and a power density of 3567W / kg (based on the mass of active materials); at -70°C, the battery operating current density can reach 0.1A / g, and achieve an energy density of 595Wh / kg and a power density of 176W / kg (based on the mass of active materials); at -86°C, the battery can operate at a current density of 0.01A / g, and achieve an energy density of 520Wh / kg (based on the mass of active materials).

[0198] Example 8

[0199] To simulate actual usage, a 5Ah lithium / carbon fluoride soft-pack battery was assembled and tested under low temperature conditions.

[0200] Positive electrode: The fluorinated carbon material, conductive carbon black (Super P) and PVDF obtained in Example 5 were uniformly mixed in a mass ratio of 9:0.5:0.5, dispersed in N-methylpyrrolidone, and fully stirred until uniform to obtain a positive electrode slurry; then the positive electrode slurry was uniformly coated on a carbon-coated aluminum foil, dried in a drying oven at 80°C for 12 hours, and then cut into 66.5×6.2 cm (length×width) long positive electrode strips.

[0201] Electrolyte: The electrolyte of Example 6 was used.

[0202] Negative electrode: A lithium ribbon with a thickness of 85 μm was cut into strips of 70.5×6 cm (length×width).

[0203] Diaphragm: PE diaphragm, SK innovation Co. Ltd.

[0204] Battery assembly: The negative electrode, separator, and positive electrode are wound into a 6.5×3.5 cm battery cell by winding, and then encapsulated with an aluminum-plastic film to obtain a 5Ah soft-pack battery.

[0205] After the assembled battery was left to rest for 24 hours, a discharge test was performed at different temperatures with a cut-off voltage of 1.5 V, and the battery's discharge specific capacity was calculated using the carbon fluoride material in the positive electrode material as the active substance.

[0206] Depend on Fig.23 It can be seen that the assembled 5Ah soft-pack battery can achieve high energy densities of 470.6Wh / kg and 332.7Wh / kg based on the overall mass at -50℃ and -70℃, respectively, showing excellent application prospects at low temperatures.

[0207] During the discharge process, Li + It undergoes the following processes: transport in the electrolyte bulk phase; desolvation at the electrode / electrolyte interface; conduction in the positive electrode solid electrolyte layer (CEI); x Interlayer diffusion; CF bond breaking. Among them, Li + Desolvation at the interface and its crossing the CEI interface layer are crucial to the low-temperature performance of the battery. Therefore, clarifying the composition and role of CEI is of great significance for the application of lithium / carbon fluoride batteries at low temperatures.

[0208] Example 9 uses the same battery as Example 7, and discharges it to different depths, disassembles it to obtain the positive electrode sheet, and uses X-ray photoelectron spectroscopy to explore the changes in CEI components during the discharge process.

[0209] Example 9

[0210] The positive electrode, electrolyte, separator, negative electrode and battery assembly method of the battery are the same as those in Example 7.

[0211] After the assembled battery was left standing at room temperature for 10 h and went through different discharge stages at 0°C, the battery was disassembled to obtain the carbon fluoride positive electrode.

[0212] Depend on Fig.24 and Fig.25 It can be seen that in Example 9, during the carbon fluoride discharge process (before 800 mAh / g), the components of the surface CEI are composed of the initial organic sulfur component (SF( Fig.24 ) and ROSOLi( Fig.25 )) dominated, gradually transformed into inorganic sulfur and inorganic fluorine components (LiF( Fig.24 ) and Li2S) are dominant, and they remain stable during the carbon fluoride discharge stage. After the carbon fluoride discharge stage, the organic sulfur component (SF( Fig.24 ) and ROSOLi( Fig.25 )) increases, corresponding to the decomposition of dimethyl sulfite, which verifies that the electrolyte provided by this patent can indeed relay the reaction after the carbon fluoride discharge platform to further improve the battery energy density.

[0213] Example 10 and Comparative Example 18 are for comparison and highlighting the function of CEI dominated by organic sulfur components corresponding to Example 9 without discharge.

[0214] Example 10

[0215] Producing CEI with organic sulfur as the dominant carbon fluoride cathode:

[0216] The positive electrode, electrolyte, separator, negative electrode and battery assembly method of the battery are the same as those in Example 7.

[0217] After the assembled battery was left standing at room temperature for 10 h, the battery was disassembled to obtain the CEI carbon fluoride positive electrode dominated by organic sulfur.

[0218] Positive electrode: The above-obtained CEI fluorinated carbon positive electrode dominated by organic sulfur

[0219] The negative electrode, separator, electrolyte and battery assembly are the same as those in Example 2.

[0220] The assembled battery was left at room temperature for 10 hours and then subjected to an AC impedance test (-20 to 25°C). The desolvation energy barrier of lithium ions was obtained by fitting the impedance spectrum.

[0221] Comparative Example 18

[0222] The positive electrode, electrolyte, separator, negative electrode and battery assembly method of the battery are the same as those of Comparative Example 4.

[0223] The assembled battery was left at room temperature for 10 hours and then subjected to an AC impedance test (-20 to 25°C). The desolvation energy barrier of lithium ions was obtained by fitting the impedance spectrum.

[0224] Depend on Fig.26 It can be seen that in the temperature range of -20 to 25 ° C, the charge transfer impedance of Example 10 is much smaller than that of Comparative Example 18, indicating that the organic sulfur-dominated CEI produced in Example 10 promotes the Li + Transmission at the interface. Further fitting of the impedance spectrum shows that ( Fig. 27 ), Li corresponding to Example 10 + The desolvation energy barrier is much smaller than that of Comparative Example 18, which verifies that the organic sulfur-dominated CEI layer produced in Example 10 can accelerate the interface reaction kinetics and improve the performance of lithium / carbon fluoride batteries at low temperatures.

[0225] Example 11 and Comparative Example 19 are contrasted to highlight the function of CEI dominated by inorganic sulfur and inorganic fluorine components produced after Example 9 is discharged for a period of time.

[0226] Embodiment 11

[0227] The positive electrode, electrolyte, separator, negative electrode and battery assembly method of the battery are the same as those in Example 7.

[0228] After the assembled battery was left at room temperature for 10 hours, it was discharged at 0°C at a current density of 0.1A / g for 1 hour. The battery was then subjected to an AC impedance test (-70 to 25°C). The desolvation barrier of lithium ions and the energy barrier of crossing the CEI were obtained by fitting the impedance spectrum.

[0229] Comparative Example 19

[0230] The positive electrode, electrolyte, separator, negative electrode and battery assembly method of the battery are the same as those in Example 7.

[0231] The assembled battery was placed at room temperature for 10 hours before AC impedance testing (-70 to 25°C). The desolvation energy barrier of lithium ions and the energy barrier of crossing the CEI were obtained by fitting the impedance spectrum.

[0232] Depend on Figures 28-29 It can be seen that the Li corresponding to Example 11 + The desolvation energy barrier and the energy barrier across the CEI layer are both smaller than those in Comparative Example 19, indicating that the CEI interface layer rich in inorganic sulfur and inorganic fluorine components corresponding to Example 11 can accelerate the reaction kinetics and further improve the performance of lithium / carbon fluoride batteries at low temperatures.

[0233] Any matters not described in the present invention are applicable to the prior art.

[0234] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A wide temperature range lithium / carbon fluoride battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode comprises a fluorinated carbon positive electrode material, and the preparation method of the fluorinated carbon positive electrode material is: Placing carbon fluoride in a plasma chemical vapor deposition furnace, maintaining vacuum, passing acetylene or methane into the plasma chemical vapor deposition furnace, controlling the radio frequency power to be 100-200W, the heat treatment temperature to be 550-600°C, and heat treating for 10-20min to obtain a carbon fluoride positive electrode material, wherein the carbon fluoride positive electrode material is a thin layer material with a surface covered with nano-carbon dots and rich in mesopores, wherein the carbon fluoride thin layer has a length and width of 5-50 μm and a thickness of 0.2-20 μm, the diameter of the nano-carbon dots on the surface of the thin layer is 5-20 nm, and the diameter of the mesopores is 2-50 nm; The electrolyte consists of lithium tetrafluoroborate, methyl acetate and dimethyl sulfite, the volume ratio of methyl acetate to dimethyl sulfite is 1:1, and the concentration of lithium tetrafluoroborate is 1 mol / L.

2. The wide temperature range lithium / carbon fluoride battery according to claim 1, characterized in that: The positive electrode is prepared by dispersing carbon fluoride positive electrode material, conductive carbon black and binder PVDF in N-methylpyrrolidone at a mass ratio of 8-9:0.5-1:0.5-1, fully mixing, coating on carbon-coated aluminum foil, and drying.

3. The wide temperature range lithium / carbon fluoride battery according to claim 1, characterized in that: The negative electrode is made of a lithium sheet or a lithium belt with a thickness of 50 to 500 μm.

4. The wide temperature range lithium / carbon fluoride battery according to claim 1, characterized in that: The separator is a PE separator with a thickness of 25 μm.

5. A positive electrode material for a wide temperature range lithium / carbon fluoride battery, characterized in that: The carbon fluoride cathode material is a thin layer material with a surface covered with nano carbon dots and rich in mesopores, wherein the carbon fluoride thin layer material has a length and width of 5 to 50 μm, a thickness of 0.2 to 20 μm, a diameter of the nano carbon dots on the surface of the thin layer of 5 to 20 nm, and a mesopore diameter of 2 to 50 nm. The preparation method is: placing carbon fluoride in a plasma chemical vapor deposition furnace, keeping the plasma chemical vapor deposition furnace vacuum by a vacuum pump; passing a carbon source atmosphere into the plasma chemical vapor deposition furnace, controlling the radio frequency power to be 50 to 200 W, the heat treatment temperature to be 300 to 600° C., and the heat treatment time to be 5 to 30 min, to obtain the carbon fluoride cathode material.

6. The positive electrode material according to claim 5, characterized in that The carbon source atmosphere is acetylene or methane.

7. The positive electrode material according to claim 5, characterized in that The radio frequency power is 100-200W; the heat treatment temperature is 550-600°C; and the heat treatment time is 10-20min.

8. A wide temperature range lithium / carbon fluoride battery electrolyte, characterized in that: The electrolyte consists of lithium tetrafluoroborate, carboxylate solvent and sulfite solvent. The carboxylate solvent is methyl formate, methyl acetate, ethyl acetate, methyl propionate and ethyl propionate; the sulfite solvent is dimethyl sulfite or diethyl sulfite.

9. The wide temperature range lithium / carbon fluoride battery electrolyte according to claim 8, characterized in that: The concentration of lithium tetrafluoroborate is 0.5-4 mol / L; the volume ratio of carboxylic acid lipid solvent to sulfite solvent is 1-0:0-1.

10. The wide temperature range lithium / carbon fluoride battery electrolyte according to claim 9, characterized in that: The concentration of lithium tetrafluoroborate is 1 mol / L, the carboxylate solvent is methyl acetate, the sulfite solvent is dimethyl sulfite, and the volume ratio of methyl acetate to dimethyl sulfite is 1:1.

Citation Information

Patent Citations

  • Noble metals coated on titanium current collectors for use in nonaqueous li / CFX cells

    CA2411087A1

  • High rate and energy cathode material for lithium batteries

    CA2788844A1

  • High rate and energy cathode material for lithium batteries

    CN103022455A

  • Lithium-ion secondary battery and electrolyte thereof

    CN103078141A

  • Lithium battery electrolyte and obtained lithium primary battery

    CN106025307A